2018
DOI: 10.23969/jrak.v10i1.1060
|View full text |Cite
|
Sign up to set email alerts
|

Pengungkapan Corporate Social Responsibility: Ukuran Dan Pertumbuhan Perusahaan, Serta Risiko Keuangan

Abstract: This research aims to determine the affect of size, growth, and leverage to the corporate social responsibility disclosure of the plantation companies in Indonesia, Malaysia, or both countries during 2013-2015. Purposive sampling method was used, obtained from 15 companies in Indonesia and 38 in Malaysia. Descriptive and multiple linear regression analysis were used in this research. The result shows that simultaneously, the size, the growth, and the leverage significantly affects CSR disclosure of the plantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
3
1
3
Order By: Relevance
“…Nevertheless, the findings of this study align with the research conducted by (Astuti et al, 2018), which state that the disclosure of CSR cannot mediate the relationship between capital structure and firm value. The findings of this research do not support the stakeholder theory, which states that firm should not operate solely for their interests, so firm need to provide benefits to many parties to create value for the firm (Octarina et al, 2018). The findings of this research do not follow the research of (Lomboan et al, 2016), which states that firm growth significantly influences firm value through CSR.…”
Section: Discussioncontrasting
confidence: 76%
“…Nevertheless, the findings of this study align with the research conducted by (Astuti et al, 2018), which state that the disclosure of CSR cannot mediate the relationship between capital structure and firm value. The findings of this research do not support the stakeholder theory, which states that firm should not operate solely for their interests, so firm need to provide benefits to many parties to create value for the firm (Octarina et al, 2018). The findings of this research do not follow the research of (Lomboan et al, 2016), which states that firm growth significantly influences firm value through CSR.…”
Section: Discussioncontrasting
confidence: 76%
“…The results of this study are in line with research by Adriana & Uswati Dewi (2019); Fahad & Nidheesh (2020); Maulia & Yanto (2020); Nur et al, (2019); Orazalin & Mahmood (2020); Solikhah & Winarsih (2016) that firm size has a positive effect on environmental disclosure. Firm size also partially possitively affect of CSR disclosure (Octarina et al, 2018). Nur et al, (2019) added that companies with high total assets would have increased market capitalization and have a high social impact on the management of company assets so that companies will carry out extensive environmental disclosures.…”
Section: Discussionmentioning
confidence: 99%
“…Companies with high asset values will make more CSR disclosures because a larger capital makes a company can carry out a CSR. Indriyani & Yuliandhari (2020); Indriyani & Sudaryati (2020); Ruroh & Latifah (2018); (Octarina et al, 2018); (Hamdani et al, 2017) suggested that company size has a positive effect on CSR disclosure.…”
Section: Methodsmentioning
confidence: 99%